Engineering Biomaterials to Direct Innate Immunity. Issue 6 (27th February 2019) - Oakes, Robert S.; Froimchuk, Eugene; Jewell, Christopher M.
Abstract: Small alterations during early stages of innate immune response can drive large changes in how adaptive immune cells develop and function during protective immunity or disease. Controlling these events creates exciting potential in the development of immune engineered vaccines and therapeutics. This progress report discusses recent biomaterial technologies exploiting innate immunity to dissect immune function and to design new vaccines and immunotherapies for infectious diseases, cancer, and autoimmunity. Across these examples, an important idea is the possibility to co‐opt innate immune mechanisms to enhance immunity during infection and cancer. During inflammatory or autoimmune disease, some of these same innate immune mechanisms can be manipulated in different ways to control excess inflammation by promotion of immunological tolerance. Abstract : Control of innate immunity is the basis of immune engineered vaccines and therapeutics . Biomaterial technologies provide modular platforms to control innate immune signals delivered alongside molecular fragments termed antigens. These antigens are processed and presented by antigen‐presenting cells (APCs) to adaptive immune cells. This biomaterial‐controlled delivery can co‐opt innate mechanisms to direct immunity and tolerance during infection, cancer, or autoimmunity.